2014
DOI: 10.2147/ott.s71646
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II alpha and TLE3 as predictive markers of response to anthracycline and taxane-containing regimens for neoadjuvant chemotherapy in breast cancer

Abstract: PurposeAnthracyclines and taxanes are considered the standard for neoadjuvant chemotherapy of breast cancer, although they are often associated with serious side effects and wide variability of individual response. In this study, we analyzed the value of topoisomerase II alpha (TOP2A) and transducin-like enhancer of split 3 (TLE3) as predictive markers of response to therapy with anthracyclines and taxanes.Materials and methodsTOP2A and TLE3 protein expressions were evaluated using immunohistochemistry on 28 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, no standard antibodies, staining procedure, and scoring system have been recommended. Various cut-off values such as 5% [ 29 ], 10% [ 30 ], 15% [ 31 ], 20% [ 26 ], and 30% [ 32 ] have been applied in different studies. Other studies took both the staining intensity and percentage of positive cells into consideration to defined TOP2A status [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no standard antibodies, staining procedure, and scoring system have been recommended. Various cut-off values such as 5% [ 29 ], 10% [ 30 ], 15% [ 31 ], 20% [ 26 ], and 30% [ 32 ] have been applied in different studies. Other studies took both the staining intensity and percentage of positive cells into consideration to defined TOP2A status [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Villanueva et al reported that TLE3 has two contradictory functions during transcriptional activity in adipogenesis [27]. TLE3 also regulates metabolism and cell fate in the bone [28,29,30], pancreas [31,32,33], muscle [34], embryonic stem cell [35,36], and cancer [17,27,37,38,39]. It is interesting to note that the relative level of TLE3 in the testes is much higher than that in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The TOP-2a gene is located on the 17q21-q22 region and is the target of anthracycline drugs. Changes in intracellular TOP-2a expression and activity form another important mechanism of breast cancer resistance to chemotherapy [ 30 ]. The HER-2 gene is located adjacent to the TOP-2a gene and promotes cell proliferation by participating in transmembrane signal transduction in a variety of ways.…”
Section: Discussionmentioning
confidence: 99%